2013
DOI: 10.1016/j.sna.2013.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Single-crystalline 4H-SiC micro cantilevers with a high quality factor

Abstract: Single-crystalline 4H-SiC micro cantilevers were fabricated by doping-type selective electrochemical etching of 4H-SiC. Using this method, n-type 4H-SiC cantilevers were fabricated on a p-type 4H-SiC substrate, and resonance characteristics of the fabricated 4H-SiC cantilevers were investigated under a vacuum condition. The resonant frequencies agreed very well with the results of numerical simulations. The maximum quality factor in first-mode resonance of the 4H-SiC cantilevers was 230,000. This is 10 times h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…SiC bulk etching techniques have been developed Figure 7. (a) 3C-SiC resonator structure [83] and (b) 4H-SiC micro cantilever [84] seeking high throughput to realize patterned, high-aspect ratio features, such as preservation of sidewall smoothness and etching profile at high etch rates, and high selectivity. In parallel, the progresses on the growth of 3C-SiC on silicon substrates and in surface micromachining techniques have enabled the fabrication of interesting MEMS devices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SiC bulk etching techniques have been developed Figure 7. (a) 3C-SiC resonator structure [83] and (b) 4H-SiC micro cantilever [84] seeking high throughput to realize patterned, high-aspect ratio features, such as preservation of sidewall smoothness and etching profile at high etch rates, and high selectivity. In parallel, the progresses on the growth of 3C-SiC on silicon substrates and in surface micromachining techniques have enabled the fabrication of interesting MEMS devices.…”
Section: Discussionmentioning
confidence: 99%
“…Adachi et al compared the resonance characteristics of 4H-SiC cantilevers on 4H-SiC substrate with the same dimensions of 3C-SiC cantilevers fabricated on Si substrate. It was observed that the resonant frequency of the 4H-SiC cantilevers was 10 times that of 3C-SiC cantilevers [84]. The 4H-SiC cantilevers were fabricated by doping-type selective electrochemical etching of 4H-SiC and their structure is shown in Figure 7(b).…”
Section: A Brief Overview Of the Most Common Sic Microsystem Devicesmentioning
confidence: 99%
“…c. Silicon carbide vacancy defects In addition to NV centres, divacancy defects of certain silicon carbide (SiC) polytypes exhibit optically addressable spin states suitable for qubit operations [47]. Furthermore, SiC micro electromechanical devices [48] and the required fabrication techniques have evolved in recent years, which could open up the possibility of a material with both optical qubit read-out and scalable fabrication techniques. Some important aspects of qubit operation, however, such as longer decoherence times (1.2 ms reported in [49]), single shot qubit read-out and deterministic defect creation with high positional accuracy have yet to be demonstrated.…”
Section: Materials Systemsmentioning
confidence: 99%
“…11 Previously, non-polymeric materials such as silicon nitride, silicon carbide, silicon dioxide and metals were very often used for fabrication of cantilevers. 1215 The overall fabrication process in case of polymeric cantilevers is substantially simplified, thus changing gears from a conventionally carried out multi-mask complex process to much easier single masking step.…”
Section: Introductionmentioning
confidence: 99%